Hybrid Rice Innovation in China: A Study of Market-Demand Induced Technological Innovation in a Centrally-Planned Economy - Lin, Justin Yifu (The Review of Economics and Statistics, 1992)
Justin Yifu Lin, Hybrid Rice Innovation in China: A Study of Market-Demand Induced Technological Innovation in a Centrally-Planned Economy, The Review of Economics and Statistics, Vol. 74, No. 1 (Feb., 1992), pp. 14-20